18q21 rearrangement and trisomy 3 in extranodal B-cell lymphomas: a study using a fluorescent in situ hybridisation technique - Tai, Y.C.; Tan, J.; Peh, S.C. (2004)
t(11; 18)(q21; q21) Translocation and trisomy 3 are the most common chromosomal aberrations reported in low-grade mucosa-associated lymphoid tissue ( MALT) lymphoma. The current study aims to investigate the frequency of these chromosomal aberrations in a series of 52 extranodal B-cell lymphomas. The tumours were categorised into three histological grades: grade 1 (low-grade lymphoma of MALT type), grade 2 diffuse large B-cell lymphoma (DLBCL) with MALT component and grade 3 ( DLBCL without MALT component). Fluorescence in situ hybridisation analyses on paraffin tissue sections were performed using a locus-specific probe for the 18q21 region and a centromeric probe for chromosome 3. The 18q21 rearrangement was detected in 9 of 40 (23%) cases, including 7 of 23 (30%) grade-1 and 2 of 11 (18%) grade-3 tumours. Amplification of the 18q21 region was detected in 10 of 40 (25%) cases, and trisomy 3 was detected in 9 of 34 (26%) cases. Amplification of the 18q21 region may be an important alternative pathogenetic pathway in MALT lymphoma and was found almost exclusively in tumours without 18q21 rearrangement. Our study showed that tumours with 18q21 rearrangement and 18q21 amplification develop along two distinct pathways, and the latter was more likely to transform into high-grade tumours upon acquisition of additional genetic alterations, such as trisomy 3. Trisomy 3 was more frequently found in coexistence with 18q21 abnormalities, suggesting that it was more likely to be a secondary aberration.